(untitled) (Journal of Management and Educational Sciences, 2024)
This study aimed to examine the relationship between the school principal’s leadership behaviors and teachers’ attitudes towards professional development according to the teachers’ opinions. The research was carried out with the relational screening model. According to the research result; the participants’ scores are related to the school principal’s leadership behaviors and teachers’ attitudes towards professional development and their general attitudes. According to the teachers who participated in the research; it is seen that the school principal’s leadership behaviors and teachers’ perceptions of their attitudes towards professional development are above the average. In the examination according to gender; no statistically significant difference was found between the school principal’s leadership behaviors and teachers’ attitudes towards professional development and their gender. In the examination according to marital status; married teachers’ perception of the school principal’s leadership behaviors was found to be higher than single teachers. In addition, single teachers’ perception of attitudes towards professional development was found to be higher than married teachers. In the examination according to educational status; teachers with master’s degrees had higher attitudes towards professional development than those with bachelor’s degrees. On the other hand, it was revealed that the perceptions of the school principal’s leadership behaviors did not change according to bachelor’s or master’s degree status. In the examination according to age groups; The perceptions of teachers between the ages of 41-50 towards professional development were higher than those between the ages of 31-40. In the examination according to the years of service; there was no statistically significant difference between the leadership behaviors of the school principal and the attitudes of teachers towards professional development and the variable of the years of service. Finally, there was no statistically significant relationship between the scores of the leadership behaviors of the school principal and the perceptions of the attitude scores of the teachers towards professional development. In addition, the total scores of the leadership behaviors of the school principal did not predict the attitudes of teachers towards professional development in a statistically significant way.